2010
DOI: 10.1073/pnas.1000293107
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the YAP-binding domain of human TEAD2

Abstract: The Hippo pathway controls organ size and suppresses tumorigenesis in metazoans by blocking cell proliferation and promoting apoptosis. The TEAD1-4 proteins (which contain a DNA-binding domain but lack an activation domain) interact with YAP (which lacks a DNA-binding domain but contains an activation domain) to form functional heterodimeric transcription factors that activate proliferative and prosurvival gene expression programs. The Hippo pathway inhibits the YAP-TEAD hybrid transcription factors by phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(196 citation statements)
references
References 39 publications
11
185
0
Order By: Relevance
“…Our study highlights the potential for YAP as a therapeutic target in ovarian cancer, particularly as reducing YAP levels can partially revert tumorigenic properties of ovarian cancer cell lines such as anchorageindependent growth, resistance to chemotherapeutic drugs, and cell migration and invasion. The TEAD1-4 transcription factors are major effectors of YAP, and the structure of YAP in complex with different TEAD family members was recently reported Li et al, 2010;Tian et al, 2010). Small molecules that inhibit the YAP/ TEAD interaction might thus prove beneficial for treatment of cancers with enhanced YAP activity, such as ovarian clear cell cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights the potential for YAP as a therapeutic target in ovarian cancer, particularly as reducing YAP levels can partially revert tumorigenic properties of ovarian cancer cell lines such as anchorageindependent growth, resistance to chemotherapeutic drugs, and cell migration and invasion. The TEAD1-4 transcription factors are major effectors of YAP, and the structure of YAP in complex with different TEAD family members was recently reported Li et al, 2010;Tian et al, 2010). Small molecules that inhibit the YAP/ TEAD interaction might thus prove beneficial for treatment of cancers with enhanced YAP activity, such as ovarian clear cell cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of YAP-TEAD interaction abolishes YAP-dependent gene transcription and largely diminishes YAP-induced cell proliferation, oncogenic transformation, and epithelial-to-mesenchymal transition (EMT) . The crystal structure of YAP-TEAD complexes reveals that the N-terminal domain of YAP wraps around the globular structure formed by the C-terminal domain of TEAD (Chen et al, 2010b;Tian et al, 2010). Particularly, a short peptide of YAP from residues 86 to 100 plays the most important role in YAP-TEAD interaction by fitting side chains into a deep pocket formed by TEAD.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…The major target transcription factors of YAP, TAZ and Yki are the four proteins of the TEA-domain-containing (TEAD) family (TEAD1-TEAD4), which correspond to a single homologue in Drosophila, Scalloped (Sd) (Goulev et al, 2008;Wu et al, 2008;Zhang, H. et al, 2009;Zhang et al, 2008;Zhao et al, 2008). Crystallographic data revealed that the N-terminal TEAD-binding domain of YAP wraps around a globular structure formed by the C-terminal domains of TEAD1, 2 and 4 Li et al, 2010;Tian et al, 2010). YAP also binds to other transcription regulators, such as Runt-related transcription factor (RUNX), the cytoplasmic domain of ErbB4 and p73, but none of these interactions has been shown so far to mediate the function of YAP in organ size control and tumorigenesis (Komuro et al, 2003;Omerovic et al, 2004;Strano et al, 2001;Yagi et al, 1999).…”
Section: Downstream Effectors Of the Hippo Pathwaymentioning
confidence: 99%